Gastrointestinal stromal tumor with secondary thrombocytosis: a case report of a high-risk patient - Li, Na; Liu, Penghui; Guo, Jiwu; Wang, Jizhen; Han, Xinling; Mao, Jie (Frontiers in Medicine, 2025)
Gastrointestinal stromal tumor (GIST) with secondary thrombocytosis is a rare clinical case, exhibiting specificity in clinical diagnosis and treatment. We report a case of GIST with secondary thrombocythemia to raise clinicians’ attention to this disease. On October 11, 2024, a 58-year-old male patient was admitted to the hospital due to “intermittent right lower abdominal pain with increased bowel movements for more than 1 month.” The patient had no prior history of tumors, chronic inflammatory diseases, hematologic disorders or family history of genetic disorders. MRI-enhanced scans of the small intestine highly indicated a lymphoma of intestinal origin. Small bowel endoscopy and pathological biopsy revealed mild chronic inflammation of the intestinal mucosa, with intact villous architecture, no plasmacytosis, granulomas, or vasculitis, and no indication of GIST. Laboratory tests showed platelet count of 909 × 109/L, white blood cell count of 11.86 × 109/L, neutrophil ratio of 75.10%, lymphocyte ratio of 15.30% and hemoglobin 101 g/L. Bone marrow biopsy microscopically showed a normal number of megakaryocytes without abnormal aggregation and no myelofibrosis, suggesting there was no obvious hematologic malignancy and the thrombocytosis may have been secondary. The patient underwent partial resection of the small intestine and resection of mesenteric lesions on October 18, 2024. The intraoperative frozen section suggested a stromal tumor. The postoperative pathological biopsy suggested a GIST and genetic testing showed a mutation in the c-KIT gene (Exon 13). Postoperatively, the patient was treated with oral imatinib mesylate (400 mg/d) as adjunctive therapy. Three months after surgery, imaging showed no recurrence, platelet decreased and returned to normal levels.